KAZACHSTANO RESPUBLIKOS ŽEMĖS TEISĖS PAGRINDINIAI PRINCIPAI - Abdraiym, B.; Saimova, Š. (Teisė, 2013)
The article deals with analysis of the principles of the land legislation of the Republic of Kazakhstan. Particular attention is given to the study of existing legislation in this area, revealing its gaps and development of recommendations and proposals aimed at improving the existing land laws.